Under-provision of private training by MENA firms: What to Do about It? - Zara Liaqat; Jeffrey B. Nugent (IZA Journal of Labor & Development, 2015)
This paper shows that firms in the Middle East and North Africa (MENA) provide training to their workers less frequently than firms in other regions and yet seem to be more in need of it. Utilizing firm level data from the Enterprise Surveys for over 100 countries, it attempts to explain that paradox and also identify alternative policy actions that MENA countries might use to substantially increase firm-supplied training by MENA firms. In particular, it points to the potential usefulness of reforms of labor regulations in MENA countries to be less rigid, but also coupling this with stronger enforcement so as to encourage existing firms to be more formal and new firms to enter, grow in size and adopt characteristics more favorable to training over time.
Keywords: J41; J58; O15; O53; 330; Training; Labor regulations; Enforcement; Middle east; Education-skills mismatch